2005
DOI: 10.1258/0268355053300857
|View full text |Cite
|
Sign up to set email alerts
|

The association between the 4G/5G polymorphism in the promoter of the plasminogen activator inhibitor-1 gene and deep venous thrombosis in young people

Abstract: Objective: To evaluate the association between the 4G/5G polymorphism in the promoter of the plasminogen activator inhibitor-1 (PAI-1) gene and deep venous thrombosis (DVT) in young people. Methods: Prevalence of the 4G/5G polymorphism was investigated using DNA analysis in a population of 81 consecutive and unrelated patients with an objectively documented first episode of DVT under 40 years old and in a control group of 88 healthy subjects. Results: The frequency of genotypes among patients was 0.27 4G/4G,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[15] In a population living in the same geographical region as ours (North of Portugal) the frequency of PAI-1 4G allele was of 76% in patients with a history of DVT before the age of 40 years and of 68% in healthy controls, this value being superior to other reports. [16] Our study has shown a very high prevalence of 4G allele in CVU patients (49 of 54 patients; 90.7%), and a significantly higher prevalence of homozygotes in patients with onset of CVU before the age of 50 years compared with later onset.…”
Section: Discussionmentioning
confidence: 46%
“…[15] In a population living in the same geographical region as ours (North of Portugal) the frequency of PAI-1 4G allele was of 76% in patients with a history of DVT before the age of 40 years and of 68% in healthy controls, this value being superior to other reports. [16] Our study has shown a very high prevalence of 4G allele in CVU patients (49 of 54 patients; 90.7%), and a significantly higher prevalence of homozygotes in patients with onset of CVU before the age of 50 years compared with later onset.…”
Section: Discussionmentioning
confidence: 46%
“…For the PAI-1 polymorphism two mixes, one for each purpose, were constituted: 2 ml genomic DNA (100 ng), 10.8 ml H 2 O, 1.6 ml MgCl 2 (3 mM), 1 ml of each primer (10 mmol), 0.8 ml of each probe (5 mmol) and 2 ml DNA-Master hybridization probes. The oligonucleotide primers and probes 18 were synthesised by TIB MOLBIOL (Berlin, Germany). The wild-type complementary detection probes 3 0 -labelled with fluorescein covered the mutation site (sensor) and the adjacent anchor probes were 5 0 -labelled with the LC-Red640 dye (anchor).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…A total of 14 studies (11,87,102,(158)(159)(160)(161)(162)(163)(164)(165)(166)(167)(168) were identified characterising the homozygous association between of the 4G allele and VTE with a pooled OR 1.20 ( 95% CI, 1.04-1.68, p=0.01; heterogeneity ([P Het ]=0.83, I 2 = 0%) (see Table 7B available online at www.thrombosis-online.com). The PAR was calculated at 4.2%…”
Section: Plasminogen-activator Inhibitor 1 (Pai-1)mentioning
confidence: 99%